Desenvolvimento e avaliação de dispositivo com fluxos rotacionais para a formação de nanofibras poliméricas pelo processo de fiação por sopro - Dulcini, Sérgio Luiz (2020)
The spinning of polymeric fibers, with micrometric and nanometric dimensions, has many technical advantages and cost benefits. The techniques known as Electrospinning and Solution Blow Spinning (SBS) have been extensively investigated because they allow production at room temperature and enable the manufacture of a greater variety of nonwovens with regard to their morphology and chemical composition as well as fiber diameter. For this reason, many researchers have sought to further understand this technology. Recent studies have been conducted on SBS with a view to increasing its productivity and controlling its processes, given that this technique allows the production of micrometric and nanometric fibers without using electric fields. The applications of nonwovens, i.e., fabrics with no orderly weave, depend on their final morphology, so it is important to understand the process of fiber formation. Published studies on SBS use linear turbulent flows to drag the polymeric solution. Changes in the process are limited to what happens in the environment after the solution is released. So far, no researchers have investigated the rotational flow inside the SBS device and at the tube outlet. Other applications have indicated that the angular velocity can assist in stretching the solution. The methodology used in this thesis consisted of electronic images and high speed cameras in addition to statistical analysis of the nanofiber diameters. The results showed a significant reduction in the average diameter of the nanofibers produced with this rotational deviceIn this study, using the biodegradable polymer poly(lactic acid) (PLA) solubilized in Dimethylcarbonate (DMC).